Fuscoporia hainanensis sp. nov. (Hymenochaetales, Basidiomycota), a new member of the F. contigua group - Chen, Qian; Liu, Lu; Zhang, De-Shun; Dong, Li-Li (Phytotaxa, 2022)
A new species, Fuscoporia hainanensis sp. nov. (Hymenochaetaceae, Basidiomycota), is decribed based on specimens from China. Phylogenetic analyses on the nLSU and ITS+nLSU+TEF1 datasets revealed that the new species was nested within the F. contigua group and formed a strongly supported lineage distinct from other species. The new species is characterized by annual, resupinate basidiocarps with medium pores (4–6 per mm), aseptate skeletal hyphae, presence of mycelial setae, hymenial setae and cystidioles, and cylindric basidiospores (5.0–6.2 × 2.3–3.0 μm). A key to the accepted period species of resupinate and mycelial setae present species of Fuscoporia is provided.